Amerykańskie korzenie kryzysu gospodarczego końca pierwszej dekady XXI wieku - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The reasons for the American crisis of the first decade of the 21st century constitute the objectives of the article. Its first part explains theoretically what crisis is with the focus on its financial character. Then, possible causes are discussed and the main ones are thought to be the following: the crisis of investments banks, unrealistic speculations, real estate market problems and the war in Iraq. The last part of the article presents briefly Paulsen’s plan.
Keywords: kryzys gospodarczy; USA; pierwsza dekada XXI w.